Pathological complete response to neoadjuvant tislelizumab plus chemotherapy in stage IIIB small cell lung cancer: A case report and literature review - Zhou, Nan; Chen, Yuhong; Huang, Qian; Jiang, Lili; Liao, Hu; Gou, Hongfeng; Lu, You; Che, Guowei; Zhang, Yan (Frontiers in Immunology, 2023)
Immunotherapy plus chemotherapy has been approved for the first-line treatment of extensive-stage small cell lung cancer (ES-SCLC, stage IV). Recently, the 2023 version of the National Comprehensive Cancer Network Guidelines recommended immunotherapy plus chemotherapy as the neoadjuvant regimen in patients with resectable non-small cell lung cancer (NSCLC). However, it is still unclear whether the combination regimen of immunotherapy plus chemotherapy is also beneficial for SCLC in the neoadjuvant context. Here, we report the case of a patient with stage IIIB SCLC who showed long-term survival and good tolerance to the neoadjuvant chemoimmunotherapy consisting of tislelizumab (an anti-PD-1 monoclonal antibody) plus etoposide-carboplatin. The patient achieved pathological complete response after receiving two cycles of neoadjuvant tislelizumab and chemotherapy followed by surgery. Two courses of postoperative tislelizumab and etoposide-carboplatin treatment was performed. The patient has survived for more than 23 months with no recurrence or metastases after neoadjuvant therapy. Multiplexed immunofluorescence and immunohistochemistry staining showed that the post-treatment specimens had remarkable immune cells infiltration, including CD3+ T cells, CD4+ T cells, CD8+ T cells, which contrasted with very low levels of these cells in the pre-treatment samples. This study is, to the best of our knowledge, the first attempt to present the neoadjuvant chemoimmunotherapy of tislelizumab in combination with etoposide-carboplatin in SCLC. Our study suggested that neoadjuvant tislelizumab plus chemotherapy may facilitate radical resection and benefit patients with locally advanced (stage IIB-IIIC) SCLC.